League redesign on the run (from Coronavirus) - Macdonald, R. D. (The Weekend Australian, 2020)
We are witnessing the biggest natural experiment in league design in Australian sporting history. Governance models are being stress-tested like never before as financial and legal relations between league administrations and clubs are reset at speed.